Improving the color of meat products without adding nitrite/nitrate using high zinc protoporphyrin IX-forming microorganisms. (March 2020) - Wakamatsu, Jun-ichi; Kawazoe, Hotaka; Ohya, Momo; Hayakawa, Toru; Kumura, Haruto
Abstract: Zinc protoporphyrin IX (ZnPP) mainly contributes to the red color of dry cured ham without nitrites/nitrates. Here, we examined the effects of acids used for pH adjustment, pH, and microorganisms on ZnPP formation. The results showed that ZnPP formation and optimal pH were dependent upon the acid type. In the presence of microorganisms, the optimal pH for ZnPP formation shifted to higher values, with the amount of formed ZnPP markedly increased at the shifted optimal pH. Additionally, two bacterial strains isolated from incubated pork homogenate exhibited an enhanced ability to form ZnPP. Although the two isolated bacteria are not edible, inoculation with one bacterium into minced meat resulted in formation of large amounts of ZnPP and color closer to that of nitrite-added meat. These results suggest that appropriate food-grade bacterial strains can improve the color of various fermented meat products in the absence of nitrites/nitrates. Highlights: Zinc protoporphyrin IX (ZnPP) formation in pork muscle is acid and pH-dependent. Microbial flora and ZnPP formation were influenced by acid used for pH adjustment. The optimal pH for ZnPP formation was dependent upon acid type and microorganisms. An inedible bacterium exhibited high ZnPP-forming and color-improving abilities. ZnPP-forming bacteria might be able to enhance dry cured meat-product color.